(3eY OQGSI MGdGJ JWHjbjI dHYV GdHdOGf GdYQHjIs - (3eYjf Gejf(B, (3GdSjOs ((3YeGf(B:s (3O(B.(3f(B,s, 2010)
(3GdGOGQI GdGSJQGJjLjI ddehGQO GdHTQjI , JNWjW GdehGQO GdHTQjI , SjGSI GdJhXja h GdeSGQ GdhXjaj , Jbjje GdhXGFa , GdJOQjH , GdbjGOI , Jbjje GdGOGA , fXe GdMhGaR (B.s
(3eQGLY U(B.383 (3; GTcGd (B:(3dcd Tcd UaMI ; LOGhd (B:(3dcd LOhd UaMIs
Keywords: (3EOGQI GdCaQGOs; (3GdEOGQIs; (3Gdbhi GdYGedIs; (3GdehGQO GdHTQjIs